2014
DOI: 10.1364/boe.5.001569
|View full text |Cite
|
Sign up to set email alerts
|

Directional sensitivity of the retina: A layered scattering model of outer-segment photoreceptor pigments

Abstract: Photoreceptor outer segments have been modeled as stacked arrays of discs or membrane infoldings containing visual pigments with light-induced dipole moments. Waveguiding has been excluded so fields diffract beyond the physical boundaries of each photoreceptor cell. Optical reciprocity is used to argue for identical radiative and light gathering properties of pigments to model vision. Two models have been introduced: one a macroscopic model that assumes a uniform pigment density across each layer and another m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 47 publications
0
57
0
Order By: Relevance
“…An in silico modeling suggested that contrast inversion of cones may results from the specific optical properties of outer segments. 23 Images very similar to negative cones have been obtained in vitro by focusing between the COST and the RPE, 24 probably because of the shorter length of the outer segment of cones. However, in our patients, defocusing did not result in a transition from positive to negative mosaic or vice versa.…”
Section: Discussionmentioning
confidence: 93%
“…An in silico modeling suggested that contrast inversion of cones may results from the specific optical properties of outer segments. 23 Images very similar to negative cones have been obtained in vitro by focusing between the COST and the RPE, 24 probably because of the shorter length of the outer segment of cones. However, in our patients, defocusing did not result in a transition from positive to negative mosaic or vice versa.…”
Section: Discussionmentioning
confidence: 93%
“…Since oblique incidence of light increases the amount of light which traverses more than one outer segment before being absorbed, this could affect the overall image quality of the cones and hence their identification with automated algorithms. However, Vohnsen [30] has previously shown that this can only have an impact when the angle of incidence on the retina is greater than 7 degrees corresponding to a pupil entrance displacement of 2.7 mm. In previous work [24], the reflectance of the cones in AO flood-illuminated images of the retinal periphery has been shown to be greatly influenced by large displacements of the entry pupil.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been several studies focused on observation of the reflectance of living cones [9,[11][12][13][14][15][16]18], and on its modelling, suggesting how the cone reflectance could be due to constructive interference of scattered light which increases with penetration depth in the cone outer segment [30], but the origin of its variability is still not fully understood. The reflectance studies have been performed with all AO imaging modalities, including AO-SLO [11][12][13]16], AO-OCT [14] and flood-illuminated AO cameras [9,17,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they have not been tested experimentally, two theories have emerged recently. One proposes that retinal cones, acting as waveguides, produce individually and in small groups of cones, different patterns of photopigment bleaching depending whether the image is formed in front of or behind the retina 28. The other novel theory proposes that the eye may obtain an odd‐error cue for accommodation from the shadows of the blood vessels on the photopigment layer of the retina 29…”
Section: Discussionmentioning
confidence: 99%